2008
DOI: 10.1097/ijg.0b013e31815c3a7f
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Primary Open-angle Glaucoma

Abstract: Aqueous humor samples may be used for determining oxidative and antioxidant status in pathologic processes. Glaucomatous eyes had a significant increase in oxidative status and decreased antioxidant activity in the aqueous humor than the cataract eyes. Oxidative stress may play a pathogenical role in the POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 29 publications
4
110
0
3
Order By: Relevance
“…28 ROS can also attack polyunsaturated fatty acids in cell membranes and induce formation of lipid peroxidation products, and MDA is a stable end product of peroxidation of lipids caused by ROS. 29 Previously, increased MDA levels were detected in several ocular diseases, including aqueous humours of patients with primary open-angle glaucoma 30 and lens epithelial cells of patient with pseudoexfoliation syndrome. 31 This is the first study to explore changes in oxidative DNA damage, lipid peroxidation, and intracellular ROS production in GO orbital fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…28 ROS can also attack polyunsaturated fatty acids in cell membranes and induce formation of lipid peroxidation products, and MDA is a stable end product of peroxidation of lipids caused by ROS. 29 Previously, increased MDA levels were detected in several ocular diseases, including aqueous humours of patients with primary open-angle glaucoma 30 and lens epithelial cells of patient with pseudoexfoliation syndrome. 31 This is the first study to explore changes in oxidative DNA damage, lipid peroxidation, and intracellular ROS production in GO orbital fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Unstable free radical species then attack cellular components causing damage to lipids, proteins, and DNA that can initiate a chain of reactions resulting in the onset of a variety of diseases, 17 including GON. [18][19][20][21] In fact, recent studies have suggested that oxidative damage constitutes an important pathologic step in inducing and maintaining the degeneration of the trabecular meshwork, optic nerve, and RGCs. Gherghel et al, for example, reported that glaucoma patients exhibit low levels of circulating glutathione, suggesting compromised oxidative defence.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the interruption of BDNF retrograde transport and the accumulation of TrkB at the optic nervehead in acute/chronic glaucoma models strongly suggest a role for neurotrophin deprivation in the pathogenesis of glaucomatous ganglion cell death . Recently it has been stressed the importance of identifying molecular biomarkers or inducers of apoptosis for better glaucoma managing (Golubnitschaja & Flammer, 2007;Zanón-Moreno & Pinazo-Durán, 2008). Therefore, different classes of molecular anomalies can be detected and utilized for glaucoma progression, among them specific molecules closely related to cell survival and apoptosis, as follows.…”
Section: Glaucoma Visual Loss and Apoptosismentioning
confidence: 99%
“…External and internal factors, as those within the retina and optic nerve ultrastructure, are important in the development and progression of primary open-angle glaucoma (POAG) (Lutjen-Drecoll et al, 1986;Hernandez et al, 1991;Triviño et al, 1996). More recent scientific knowledge revealed a complex situation in which other factors, as the circulatory (Yanagi et al, 2010), inflammatory (Kumarasamy et al, 2006), toxicologic (Schori et al, 2001), biochemical and molecular (Zanón-Moreno & Pinazo-Durán, 2008;Zanón-Moreno et al, 2008Ray & Mookherjee, 2009, Osborne, 2010, are likely to be involved in the pathogenesis of glaucomatous optic neuropathy. Whatever may be the real factors involved in glaucoma pathogenesis, the glaucomatous eyes suffer the dysfunction and death of the retinal ganglion cells leading to optic atrophy and irreversible visual loss.…”
Section: Introductionmentioning
confidence: 99%